Physiotherapy Management of Humeral Shaft Fracture; Case study - Nafiah Nafiah Nafiah; Nurul Aini Rahmawati; Zaimah Zaimah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Humeral Shaft Fractures represent approximately 1% to 5% of all fractures occurring between 13 and 20 per 100,000 people annually. The problems experienced by patients after plate and screw installation of Humeral Shaft Fractures include pain due to incision wounds, limited joint movement, muscle weakness and reduced functional ability. This type of research is a case study conducted at Departement rhysiotherapy ULIN Hospital, Banjarmasin. The research due on August 2023. The subject of this research was a 25 year old who experienced Humeral Shaft Fractures used NMES, passive and active exercise. A week after the plate and screw installation operation, the patient experienced swelling around the incision, pain, weakness, difficulty moving and stiffness. After physiotherapy and evaluation, the results showed an improvement in edema, decreased pain, increased muscle strength and increased LGS after being given NMES, passive intervention. and active exercise.